TEACHING AND TRANSFERING MATERIAL (TTM) SEBAGAI MODEL PEMBELAJARAN KOLABORATIF UNTUK MENINGKATKAN HASIL BELAJAR PADA MATERI TEKS DRAMA DI KELAS VIII.5 SMP NEGERI 15 PALEMBANG - Nisphi, Medio Lailatin (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sriwijaya, 2023)
This Collaborative Classroom Action Research (CCAR) aims to improve students' Bahasa Indonesia outcomes by applying the transferring and teaching material (TTM) model to learning drama texts in Class VIII.5 of SMP Negeri 15 Palembang. The action implementation procedure is an activity cycle consisting of four stages, namely (1) planning, (2) implementation, (c) observation, and (d) evaluation and reflection. The data obtained are learning outcomes that are analyzed descriptively. Based on the results of data analysis, it was found that there was an increase in the percentage of completeness of student learning outcomes from Cycle I by 28%, while in Cycle II, it reached 66%, and in Cycle III, it reached 86%. However, the reflection results showed there were still existing weaknesses, so it was continued in cycles IV and V, reaching 100%. Therefore this learning model of transferring and teaching material (TTM) can be used as an alternative for teachers to improve the learning outcomes of Indonesian junior high school students.